Evaluation of Public-Private Partnerships in Employment Programs in Azerbaijan - Honaryar, Zabihullah; Hasanli, Safa; Babazada, Fatima (ADA University, 2024)
While Public-Private Partnerships (PPP) has the potential to play a significant role in tackling employment challenges, it is facing considerable drawbacks in the context of Azerbaijani society. Among many problems, this capstone project examined education and labor market mismatch, the lack of public and private agencies’ involvement in the education system, and the low reputation of vocational education. To address these shortcomings, the study suggests alternative policies including regular market assessment for collecting, analyzing, and utilizing labor market data, establishing a dynamic and effective collaboration between stakeholders, forming a specific and well-regulated legal framework for the education sector within the newly adopted Law on PPP, and improving vocational education. All the suggested policies are evaluated against five criteria including efficiency, effectiveness, feasibility, flexibility, and equity to measure the possibility of success in practical implementation and to choose the best option. The project employed both qualitative and quantitative methodologies to collect appropriate primary data by conducting surveys, interviewing experts in the field, and utilizing related secondary hand data. The assessments and analyses suggest that improving employment programs using PPP initiatives, a comprehensive approach that involves policy adjustments, collaboration between stakeholders, and ongoing monitoring and evaluation is required.
Keywords: Public-private partnerships; Employment -- Azerbaijan; Vocational education -- Azerbaijan; Education -- Government policy -- Azerbaijan; Public-private sector cooperation; Workforce development; Public and International Affairs